Successful Term Pregnancy in a Second Trimester Female with Urosepsis: A Case Report - Mishra, Vineet V (J Clin Diagn Res, 2015)
Urolithiasis means calculus in urinary system. It is a rare condition in pregnancy which can have devastating results for the mother in the form of pyonephrosis and septicaemia and to the foetus in the form of IUGR and prematurity. This is a rare case report of a 27-year old female patient who presented with perinephric abscess and hydronephrosis at 22 weeks of pregnancy. With proper evaluation and management, pregnancy continued till term with good perinatal outcome.